2016
DOI: 10.3390/molecules21050602
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Epididymal Luminal Fluid Proteins Involved in Sperm Maturation in Infertile Rats Treated by Dutasteride Using iTRAQ

Abstract: Background: Spermatozoa become mature and acquire fertilizing capacity during their passage through the epididymal lumen. In this study, we identified new epididymal luminal fluid proteins involved in sperm maturation in infertile rats by dutasteride, a dual 5α-reductase inhibitor, in order to provide potential epididymal targets for new contraceptives and infertility treatment. Methods: Male rats were treated with dutasteride for 28 consecutive days. We observed the protein expression profiles in the epididym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
5
10
1
Order By: Relevance
“…The results of present study showed no significant changes in final body and testis weights with significant decreases in the weights of the DHT-dependent tissues such as epididymis, seminal vesicle or VP of male BALB/c mice treated with DS compared to controls. Our results are in agreement with findings of Henderson et al (2004) and by Xie et al (2016) in male rats after treatment with DS. The slight reduction in body weights of NF-treated mice is in accordance with results of Lee et al (2006) in NF-treated ICR male mice.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The results of present study showed no significant changes in final body and testis weights with significant decreases in the weights of the DHT-dependent tissues such as epididymis, seminal vesicle or VP of male BALB/c mice treated with DS compared to controls. Our results are in agreement with findings of Henderson et al (2004) and by Xie et al (2016) in male rats after treatment with DS. The slight reduction in body weights of NF-treated mice is in accordance with results of Lee et al (2006) in NF-treated ICR male mice.…”
Section: Discussionsupporting
confidence: 94%
“…Sperm functions such as count and motility are key indices of male fertility as these are prime markers in testicular spermatogenesis and epididymal sperm maturation. The significant decline in sperm count of caput and cauda epididymides of DS-and NF-treated mice in current study are in accordance with findings reported by Henderson and Robaire (2005) and by Xie et al (2016) in DS-treated rats. The reduced sperm count of cauda epididymis in NF-treated mice is in accordance with findings of Morakinyo et al (2009) in NF-treated rats.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The peptide mixture was loaded onto a C18-reverse phase column (15 cm long, 75 µm inner diameter, RP-C18 3 µm, packed in-house) in buffer A (0.1% formic acid) and separated with a linear gradient of buffer B (80% ACN, 0.1% formic acid) at a flow rate of 250 nl/min controlled by IntelliFlow technology over 240 min. The peptides were eluted with a gradient of 0–55% buffer B for 220 min, 55%–100% buffer B for 8 min and held in 100% buffer B for 12 min [20]. For MS analysis, peptides were analyzed in positive ion mode.…”
Section: Methodsmentioning
confidence: 99%